Light touch induces ERK activation in superficial dorsal horn neurons after inflammation: involvement of spinal astrocytes and JNK signaling in touch-evoked central sensitization and mechanical allodynia - Gao, Yong-Jing (2010)
Activation of extracellular signal-regulated kinase (ERK) in spinal cord neurons could serve as a marker for sensitization of dorsal horn neurons in persistent pain. ERK is normally activated by high-threshold noxious stimuli. We investigated how low-threshold mechanical stimuli could activate ERK after complete Freund’s adjuvant (CFA)-induced inflammation. Unilateral injection of CFA induced ipsilateral heat hyperalgesia and bilateral mechanical allodynia. CFA-induced ERK activation in ipsilateral dorsal horn neurons declined after 2 days. Interestingly, low threshold mechanical stimulation given by light touch either on the inflamed paw or the contralateral non-inflamed paw dramatically increased ERK phosphorylation (pERK) in the dorsal horn ipsilateral to touch stimulation. Notably, light touch induced pERK mainly in superficial neurons in laminae I-IIo. Intrathecal administration of the astroglial toxin L-α-aminoadipate (L-α-AA) on post-CFA day 2 reversed CFA-induced bilateral mechanical allodynia but not heat hyperalgesia. Furthermore, L-α-AA, the glial inhibitor fluorocitrate, and a peptide inhibitor of c-Jun N-terminal Kinase (JNK) all reduced light touch-evoked ERK activation ipsilateral to touch. Collectively, these data suggest that (a) ERK can be activated in superficial dorsal horn neurons by low threshold mechanical stimulation under pathological condition and (b) ERK activation by light touch is associated with mechanical allodynia and requires an astrocyte network.